DEVELOPMENT OF CONSUMER BASKETS FOR THE POPULATION: INTERNATIONAL EXPERIENCE AND NATIONAL PRACTICE - Irina Evdokimovna Dolgova (Ecomind Press, 2025)
This research article is devoted to the study of the development of consumer baskets worldwide. The formation of a consumer basket is an important tool of social policy, reflecting the standard of living and the minimum needs of the population. The article examines theoretical and methodological approaches to the development of consumer baskets in various countries, including differences in structure, composition, and calculation methods. International practices are analyzed with an emphasis on a comparative approach to defining basic consumption standards. Particular attention is given to the national practice of forming the consumer basket in the Republic of Uzbekistan: its features, regulatory foundations, and existing problems are identified. Based on comparative analysis, the article offers recommendations for improving the methodology for calculating the consumer basket, taking into account international experience and the socio-economic realities of the country.
Keywords: Food basket, consumer basket of the population, minimum level of consumption, rational norms of food consumption, international experience, national practice.